Soobstoj oblikovanja, regulativnega okvira in pogajanj na področju urbanističnega načrtovanja - Ultramari, Clovis (Urbani izziv, 2023)
Studies commonly reiterate that urban planning complexity is defined by the coexistence of three elements: regulation, various scales of urban design, and multiagent negotiations. We confirm this; however, we reject the idea that they can ideally interact in perfect balance with no negative impact on each other. Thus, this article analyses the limits of coexistence of these elements. We hypothesize that perfect and balanced coexistence is not possible. This is based on four main and consecutive activities: 1) a literature review concerning the roots we believe contemporary urban planning is based on; 2) a critical and qualitative analysis of the main documents containing urban planning directives currently in use by the three largest cities in Latin America (Buenos Aires, Mexico City, and Sao Paulo) focused on the guidelines established by these documents and how they communicate with each of the three pillars; 3) identification of controversies and convergences in the interaction between the three pillars; and 4) elaboration of conclusions.
Keywords: collaborative urban planning; participativni urbanizem; urban planning concepts; urban planning theories; urbanistične teorije; urbanistični instrumenti; urbanistični pojmi